SOME IDEAS FOR TEACHING GRAMMAR MORE EFFECTIVELY IN AN EFL CONTEXT - Christopher B. Allen B. Allen (Universitas Katolik Indonesia Atma Jaya, 2005)
Most teachers in an EFL context place a great importance ongrammar and see their primary function as reducing their students’grammar errors. While ignoring the value of this attitude, thisarticle sets out to show how teachers’ view of grammar is limitingand their approach to teaching grammar Keywords: collocations, extensive reading, grammar oforientation, grammar of structure, notice-the-gaps,noticing, pattern grammar, PPP lesson plan,production-practice, scaffolding, task-basedapproach.